Analisis Kasus Ujaran Kebencian Mizan Qudsiah Penghina Makam Keramat Lombok - Muhammad Faozan (TAFAQQUH, 2022)
This research aims to analyze the meaning of “hatred and inter-group relations” as described in Article 28, Section (2) of Indonesia’s Information and Electronic Transactions (ITE) Law, assessing its compliance with Indonesia’s positive legal framework, with a focus on definitional ambiguities and potential for multiple interpretations that impact legal certainty. Using a normative analysis approach, examining related articles and case studies within Indonesian jurisprudence, this study finds that the lack of clarity in the article's formulation leads to varying interpretations, particularly regarding the terms "hatred" and "inter-group." Findings indicate that the article is vulnerable to being used as a tool to silence criticism, thus conflicting with the principles of Lex Certa and Lex Stricta, which mandate precision and clarity in legal drafting. This research contributes by recommending a reformulation of the article to ensure fair legal application and to prevent misuse within the law enforcement process in Indonesia.